A Case Study On Commerce International Merchant Bank Group, CIMB Group - Wen, Eda Ong Jing (2009)
This paper examines macro-environmental and micro-environmental factors that affect the performance and sustainability of Commerce International Merchant Bank (CIMB) Group. It also examines the macro-environmental factors of CIMB Group through SEPT analysis, where analysis on the social, economic, political and technological environment was performed